Characteristics and outcomes of individuals screening positive for borderline personality disorder on an adult inpatient psychiatry unit: a cross-sectional study - Joann J. Chen; Sam A. Mermin; Lucie A. Duffy; Samantha A. Wong; Savannah D. Layfield; Fernando Rodriguez-Villa; Steven E. Gelda; Eliot M. Gelwan; Jane Eisen; Kerry J. Ressler; Lois W. Choi-Kain; Agustin G. Yip (BMC Psychiatry)
Abstract Background Outpatient psychotherapies are gold standard interventions for borderline personality disorder (BPD); however, in clinical reality, higher rates of psychiatric hospitalization and more severe symptoms, including suicidality and self-harm, occur for those with BPD compared to those with other psychiatric disorders in inpatient units. Methods This study aims to distinguish the clinical profile and outcomes of patients screening positive for a threshold of BPD traits in the inpatient psychiatric setting using the McLean Screening Instrument for Borderline Personality Disorder (MSI-BPD), from those who do not. Results Compared to those screening negative on the MSI-BPD (MSI-BPD-), those who screen positive (MSI-BPD +) are younger, more likely to be female, and more likely to report a range of health and psychosocial risk factors such as unstable housing, reduced educational attainment, physical health problems, past trauma, and problematic drug and alcohol use. MSI-BPD + patients report significantly higher severity of anxiety, depression, suicidality, self-harm, and global symptoms on admission than MSI-BPD- patients. In terms of response to inpatient care, they also self-report significantly greater improvements and higher proportions of reliable change on measures of anxiety, depression, and general psychiatric severity. At discharge, MSI-BPD + patients no longer report significantly higher suicidality but do report greater levels of thoughts of self-harm. Conclusions These findings suggest that patients with self-reported BPD symptoms experience acute symptom relief during short-term inpatient hospitalization, including for suicidality-related symptoms. Our study also demonstrates the feasibility of utilizing the MSI-BPD screening tool within a large adult inpatient psychiatric population to identify individuals likely to have BPD with distinct clinical profiles.